Anxiety, depression, and quality of life among HIV positive injection drug users in Ukraine, 2017 - Vasylyev, Marta; Davtyan, Hayk; Denisiuk, Olga; Chadwick Jayaraj, Joshua; Koval, Tetyana; Piddubna, Anna; Sluzhynska, Maryana; Sluzhynska, Oleksandra; Mulcahy, Fiona (The Journal of Infection in Developing Countries, 2019)
Introduction: People who inject drugs (PWID) are one of the key populations most vulnerable to HIV infection, with 28 times higher prevalence compared to the rest of the population. PWID are known to have many physical, psychological and lifestyle challenges that can influence access to care. Depression is common among PWID living with HIV. It has major effect on health-related quality of life (HRQoL) and is influencing adherence to antiretroviral therapy. This study was conducted to explore how anxiety and depression affect HRQoL among HIV-positive PWID in Ukraine. It will provide knowledge for the further policy development. Methodology: A descriptive cross-sectional study using data from interviewer- administrated questionnaires was performed. The questionnaire was based on the Hospital Anxiety and Depression Scale. The questionnaire on HRQoL was based on the SF-36. Results: Among the 90 HIV positive PWID 74% (67) and 61% (55) had anxiety and depression scores higher than 7 respectively, indicating that most patients had mental health problems. Average scores for general health (40), role limitations due to physical (44) and emotional health (34), vitality (41) and mental health (45) had mean scores less than 50 along with total physical (43) and mental health scores (35). Having an HIV positive partner or partner with unknown HIV status increases anxiety in HIV positive PWID. Conclusion: There are increased depressive and anxiety symptoms and poorer QoL among HIV-positive PWID in Ukraine. Strategies focusing on psychosocial support addressing QoL as part of HIV care could improve health outcomes for these comorbid and debilitating conditions.